Deciphering the Green Marketing Puzzle: Understanding the Interplay of Green Marketing Strategic Orientation, Attitude towards Green Marketing, Brand Integrity, and Purchase Intention - Putra, Aditya Halim Perdana Kusuma; Mariam, Siti; Tafsir, Moh.; Rosanti, Novita (International Review of Management and Marketing, 2024)
The purpose of this study aims (1) Investigate the role of the item constructs access to information, labelling and peer pressure, sense of retribution, and circular economy perception on green individuals feelings; (2) Evaluate the role of green business orientation and product quality on perceived of green marketing strategic orientation through the second-order analysis test. As a design methodology we involved 178 respondents at Starbucks outlets in Makassar City, Indonesia, with purposive random sampling. The analysis was conducted through a second-order analysis approach to test the variable constructs and through direct and indirect testing by involving attitude towards green marketing and brand integrity as intervening variables. The result of this study shows all items have a significant role in shaping the perceived of green marketing strategic orientation and green individuals feelings through the second-order analysis approach. Direct test showed a positive and significant effect except in the relationship between perceived of green promotion and innovation and brand integrity. Indirect test shows that the relationship between perceived of green marketing strategic orientation, perceived of green promotion and innovation, and purchase intention with attitude towards green marketing as an intervening variable is not significant. Similarly, the relationship between green individuals feelings, purchase intention, brand integrity, and perceived of green promotion and innovation as intervening variables is also not significant.